Candida tropicalis systemic infection redirects leukocyte infiltration to the kidneys attenuating encephalomyelitis - Munhoz-Alves, Natália [UNESP]; Mimura, Luiza Ayumi Nishiyama [UNESP]; Viero, Rosa Marlene [UNESP]; Bagagli, Eduardo [UNESP]; Peron, Jean Pierre Schatzmann; Sartori, Alexandrina [UNESP]; Fraga-Silva, Thais Fernanda de Campos [UNESP] (MDPI, 2021)
Environmental factors, including infections, are strongly associated with the pathogenesis of multiple sclerosis (MS), which is an autoimmune and demyelinating disease of the central nervous system (CNS). Although classically associated with bacterial and viral agents, fungal species have also been suspected to affect the course of the disease. Candida tropicalis is an opportunistic fungus that affects immunocompromised individuals and is also able to spread to vital organs. As C. tropicalis has been increasingly isolated from systemic infections, we aimed to evaluate the effect of this fungus on experimental autoimmune encephalomyelitis (EAE), a murine model to study MS. For this, EAE was induced in female C57BL/6 mice 3 days after infection with 106 viable C. tropicalis yeasts. The infection decreased EAE prevalence and severity, confirmed by the less inflammatory infiltrate and less demyelization in the lumbar spinal cord. Despite this, C. tropicalis infection associated with EAE results in the death of some animals and increased urea and creatinine serum levels. The kidneys of EAE-infected mice showed higher fungal load associated with increased leukocyte infiltration (CD45+ cells) and higher expression of T-box transcription factor (Tbx21) and forkhead box P3 (Foxp3). Altogether, our results demonstrate that although C. tropicalis infection reduces the prevalence and severity of EAE, partially due to the sequestration of leukocytes by the inflamed renal tissue, this effect is associated with a poor disease outcome.
Keywords: Autoimmunity; Candida spp; Candida tropicalis; Multiple sclerosis